Cost effectiveness of cotrimoxazole and ampicillin on urinary tract infection in children on direct medical aspect - Dyah Harini Dyah Harini (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: Urinary tract infection (UTI) is one of the important diseases causing significant morbidity in infants and children. The true incidence of UTI in children is difficult to estimate because infection in infants and children can be asymptomatic. Delay in the treatment of UTI can lead to recurrent infection resulting in renal scarring or complication with urosepsis. Physicians use a large number of different antimicrobials and give them for widely varying durations to children and infants with suspected UTI. More standardized use of the most effective, best tolerated and least costly treatment regimens would have considerable benefit both in reducing morbidity and health care costs.Objective: The aim of this study is to compare of ampicillin compared to cotrimoxazole oral treatment in UTI children's.Methods: This study was used clinical trial design. A total of 1-10 child patients in Dr. Sardjito Hospitalwith urinary tract infection older than 2 months age who enaolled in this study were randomly assigned to receive either ampicillin (57 children) or cotrimoxazole (53 children). Diagnosis was based on clinical and laboratory criteria. Laboratory diagnosis was established based on bacterial count and urine culture tests. The cure rates were assessed after seven day treatment based on clinical and laboratory evalua- tion. Chi-square test was applied to analyse the difference of clinical outcomes between ampicillin and cotrimoxazole groups. Logistic regression analysis was applied to analyse the relationship of variable that influence the outcomes. Cost analysis accounted by direct cost (medical, length of stay, laboratory cost)between two groupsResult: Mean of the length of stay of cotrimoxazole patient was shorter than ampicillin patients. It was also found that E coli was the most frequent (45.4%) microbes detected in the urine culture. There were no significant differences in the sensitivity of the microbes to both antibiotics. The results indicated that cotrimoxazole showed significant differences in the effectiveness (p<0.05).Conclusion: Cotrimoxazole treatment on UTI is as effective as ampicillin. Cotrimoxazole costs cheaper.Key words: ampicillin- cotrimoxazole - cost- urinary tract infection- cure rate- urine culture- bacterialcount